The impact of a printed educational booklet on disease awareness in women with gestational diabetes. (20th October 2021) - Staynova, R; Vasileva, E; Stankova, T; Yanachkova, V
Abstract: Background: Gestational diabetes mellitus (GDM) is a major health concern which could lead to adverse pregnancy outcomes. Women with newly diagnosed GDM need additional information and education about this pregnancy complication. The aim of current study was to evaluate the impact of a printed educational booklet on disease awareness in women with GDM. Methods: One hundred and thirty-five pregnant women with newly diagnosed GDM who attended antenatal clinic were randomly assigned to either an intervention (n = 45) or a control group (n = 90). The women from intervention group received additional printed educational booklet about GDM management, while patients from the control group received standard care. The booklet includes information about risk factors, treatment alternatives, self-monitoring of blood glucose, nutritional management and lifestyle modification. After one month a self-administered written questionnaire was used for evaluation of women's knowledge about GDM management. Descriptive statistics and chi-square test were used to analyse the data. Results: Demographic and maternal characteristics were similar in both groups. The overall mean age was 32.3 years ranging from 24 to 45. The correct answers about diabetes complications awareness were reported in more than 50% of women in both groups. There was a significant difference in knowledge about the risk factors for GDM (85% in the intervention group versus 44% in the control group, P < 0.001). The number of correct answers was higher in the intervention group regarding GDM treatment (92% compared to 79% in the control group, P < 0.01), self-monitoring of blood glucose and outcomes of GDM (P < 0.001). The differences in nutritional knowledge were not statistically significant. Conclusions: The results from the study show that printed educational materials can improve patients' knowledge about GDM management as well as their health literacy and motivation. Key messages: Providing a printed educational booklet in addition to standard pregnancy care for women with GDM may be beneficial for achieving therapeutic goals. The booklet used in this study could assist healthcare providers in improving the knowledge and educational process of women with GDM.